Snow on the pine : Japan's quest for a leadership role in Asia - Hatakeyama, Kyoko (World Scientific, 2010)
""Snow on the Pine"" presents a compelling view of the Japanese foreign policy that runs counter to the common wisdom reducing Japan's post-war efforts to the pursuit of purely commercial interests. This book takes a new approach - the eventual Japanese defeat in the Second World War did not transform Japan into an exceptional state seeking only economic interests. Like any other nations, economic issues have always played a crucial role in policy decisions. However, this is but only one amongst the many interweaving threads determining foreign policy decisions. In the authors' eyes, Japan's f